Assistance in the Implementation of Madrasah-Based Management at the Madrasah Tsanawiyah Ummul Quran An-Nurani Tembilahan - Nurmadiah, Nurmadiah; Suryani, Suryani; Nurgaya, Siti; Suhana, Suhana; Khairunnisa, Khairunnisa; Sela, Nur; Selfi, Selfi (Jurnal Masyarakat Mengabdi, 2024)
The aim of this service activity is to implement madrasa-based management by interns at MTs Ummul Quran An-Nurani Tembilahan, the method used in this activity is mentoring, and interviews with the head of the madrasah for this service activity. With full dedication and commitment, the interns have succeeded in devoting themselves to implementing madrasa-based management at MTs Ummul Quran An-Nurani Tembilahan well. Through collaborative efforts and hard work, they have succeeded in integrating the principles of Islamic education into the daily management of the school. Intern participants have demonstrated a deep understanding of the madrasa's vision, mission and values, and are able to design and implement appropriate strategic steps to strengthen the identity and improve the quality of Islamic education in the school. By taking detailed planning steps, organizing various activities, and conducting thorough evaluations, they have helped create a learning environment that is conducive and supportive for holistic student growth and development. The results of their dedication are seen in continuous improvements in various aspects of school life, including academic aspects, leadership, discipline, and student participation in extracurricular activities oriented towards the development of Islamic values. In this way, the interns have proven themselves to be effective agents of change in advancing the vision and mission of madrasa education at MTs Ummul Quran An-Nurani Tembilahan.